2015
DOI: 10.1089/gtmb.2014.0210
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA-367 Inhibits the Invasion and Metastasis of Gastric Cancer by Directly Repressing Rab23

Abstract: Our study shows that miR-367 is a key negative regulator of the invasion and metastasis of gastric cancer and establishes a strong rationale for developing miR-367 as a novel therapeutic agent against gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 20 publications
1
36
1
Order By: Relevance
“…However, in contrast to these oncogenic characteristics, miR-367 is downregulated in gastric cancer (Bin et al, 2015), glioma (Guan et al, 2015), and cervical carcinoma (Cai et al, 2013). Reduced miR-367 expression in gastric cancer tissues correlates with tumor metastasis and advanced tumor-node-metastasis stage (Bin et al, 2015), and its overexpression has been shown to inhibit gastric cancer cell invasion via direct suppression of Rab23 (Bin et al, 2015). Ectopic expression of miR-367 restricts proliferation and blocks the G1/S transition of cervical cancer cells through regulation of AKT1 (Cai et al, 2013), and low miR-367 level is an independent indicator of unfavorable prognosis for glioma patients (Guan et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, in contrast to these oncogenic characteristics, miR-367 is downregulated in gastric cancer (Bin et al, 2015), glioma (Guan et al, 2015), and cervical carcinoma (Cai et al, 2013). Reduced miR-367 expression in gastric cancer tissues correlates with tumor metastasis and advanced tumor-node-metastasis stage (Bin et al, 2015), and its overexpression has been shown to inhibit gastric cancer cell invasion via direct suppression of Rab23 (Bin et al, 2015). Ectopic expression of miR-367 restricts proliferation and blocks the G1/S transition of cervical cancer cells through regulation of AKT1 (Cai et al, 2013), and low miR-367 level is an independent indicator of unfavorable prognosis for glioma patients (Guan et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, this miRNA suppresses Adriamycininduced apoptosis of osteosarcoma cells by targeting KLF4 (Wang et al, 2016). However, in contrast to these oncogenic characteristics, miR-367 is downregulated in gastric cancer (Bin et al, 2015), glioma (Guan et al, 2015), and cervical carcinoma (Cai et al, 2013). Reduced miR-367 expression in gastric cancer tissues correlates with tumor metastasis and advanced tumor-node-metastasis stage (Bin et al, 2015), and its overexpression has been shown to inhibit gastric cancer cell invasion via direct suppression of Rab23 (Bin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 60% of human protein-coding genes contain at least one conserved miRNA -binding site, and considering that numerous non-conserved sites also exist, most protein-coding genes may be under the control of miRNAs [9]. A lot of study suggested that miRNA plays crucial roles in many biological processes such as development, inflammation, differentiation, cell proliferation, apoptosis and invasion [10][11][12][13]. Thus, their dysregulation is often associated with human diseases, including cancer and neurodevelopmental disorders [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that miR-367 participates in the tumorigenesis of various types of cancers, such as hepatocellular carcinoma (5), medulloblastoma (6) and pancreatic cancer (7). In contrast, in the study of gastric carcinoma, miR-367 inhibited cell migration and invasion, and its expression in cancer tissues was much lower than that in normal stomach tissues (8). This implied that miR-367 may play different roles in various tumors.…”
Section: Introductionmentioning
confidence: 99%